Genomic EWS-FLI1 Fusion Sequences in Ewing Sarcoma Resemble Breakpoint Characteristics of Immature Lymphoid Malignancies - Berger, Manfred (Public Library of Science, 2013)
Chromosomal translocations between the EWS gene and members of the ETS gene family are characteristic molecular features of the Ewing sarcoma. The most common translocation t(11;22)(q24;q12) fuses the EWS gene to FLI1, and is present in 85–90% of Ewing sarcomas. In the present study, a specifically designed multiplex long-range PCR assay was applied to amplify genomic EWS-FLI1 fusion sites from as little as 100 ng template DNA. Characterization of the EWS-FLI1 fusion sites of 42 pediatric and young adult Ewing sarcoma patients and seven cell lines revealed a clustering in the 5′ region of the EWS-breakpoint cluster region (BCR), in contrast to random distribution of breakpoints in the FLI1-BCR. No association of breakpoints with various recombination-inducing sequence motifs was identified. The occurrence of small deletions and duplications at the genomic junction is characteristic of involvement of the non-homologous end-joining (NHEJ) repair system, similar to findings at chromosomal breakpoints in pediatric leukemia and lymphoma.